A REVIEW OF SOME CONTENTIOUS ISSUES IN ELECTORAL MATTERS IN NIGERIA1 - IGUH, IGUH; ADAORA, AMAKA (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
The laws that govern elections in Nigeria are the Constitution2and the Electoral Act.3The Constitution is the supreme and most important law of the country. Section 1 (3)4makes it clear that if any other law is inconsistent with the provisions of the constitution that other law shall be void to the extent of the inconsistency. The courts have also upheld that section in countless decisions5for this reason alone any law dealing with elections that contradicts the provisions of the Constitution will be of no effect. The Constitution also provides clearly that the Government of Nigeria or any part thereof shall not be governed or controlled by any person or group of persons except in accordance with the provisions of the Constitution.6In other words, no one can occupy elective offices at the local, state or federal level unless he or she has been elected in accordance with the provisions of the Constitution or any law made in accordance with the Constitution. Apart from the laws on election, electoral bodies are equally established to help in conducting election in Nigeria. There are various contentious issues in our electoral matters which have not been resolved by the legislators. Some which the legislators tried to resolve by enactment of laws, but which still have some aspects to be looked into. These issues are numerous but the writer will review some of them.